2013
DOI: 10.7860/jcdr/2012/5104.2702
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and its Oral Outcome – A Review

Abstract: Malnutrition affects the oral health and a poor oral health in turn, may lead to malnutrition. This interdependent relationship sees good nutritional health, thus promoting good oral health and vice versa. Malnutrition may alter the homeostasis, which can lead to disease progression of the oral cavity, reduce the resistance to the microbial biofilm and reduce the capacity of tissue healing. It may even affect the development of the oral cavity. Protein-energy malnutrition occurs when there is a deficiency of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
112
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 19 publications
3
112
0
6
Order By: Relevance
“…In children body weight influences mediator like adipocytokines that have been traditionally tought to be involved in inflammatory process which furthermore may be a risk for development of any systemic diseases evidently will determine general health status [9]. Various studies have proven that the nutritional status of a child who can be identified through BMI determination is very influential on oral health status including dental health status and periodontal health status identified by debris index and calculus index [10]. Ekuni et al conducted the study showing that BMI as presentation of general health status has strongly connection with periodontitis exhibiting oral health status represented by OHI-S [11].…”
Section: Resultsmentioning
confidence: 99%
“…In children body weight influences mediator like adipocytokines that have been traditionally tought to be involved in inflammatory process which furthermore may be a risk for development of any systemic diseases evidently will determine general health status [9]. Various studies have proven that the nutritional status of a child who can be identified through BMI determination is very influential on oral health status including dental health status and periodontal health status identified by debris index and calculus index [10]. Ekuni et al conducted the study showing that BMI as presentation of general health status has strongly connection with periodontitis exhibiting oral health status represented by OHI-S [11].…”
Section: Resultsmentioning
confidence: 99%
“…Also, the gonial° angle was decreased in low-SES children. This could be the result of delayed eruption of the first permanent molars, 25 or due to a late exfolation related to malnutrition 26 reducing the size of this angle. According to clinical, cephalometric and model analyses, the main classification observed was a dental AOB in 64.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies have shown that deficiencies in protein, minerals and vitamins in the perinatal period are related to changes in the development of the teeth (enamel hypoplasia and hypocalcification) and supporting structures, salivary glands, and delays in the chronology of eruption in children [20]. These conditions have been associated with an increased susceptibility of teeth to caries [21].…”
Section: Discussionmentioning
confidence: 99%